Assessing the Relationship Between Temporomandibular Joint Disorders and Foot Weight-Bearing Changes: A Sensor Plate-Based Observational Study. - Khan, Jafar; Baghela, Vinita; Warsi, Rahat Khan; Nagar, S. B.; Ramawat, Prashant; Khan, Usmaan; Naqvi, Saleem Akhtar; Goyal, Bhupesh (Journal of Neonatal Surgery, 2025)
Background: Temporomandibular joint (TMJ) disorders are among the most prevalent musculoskeletal conditions and may influence posture and distal biomechanics through the kinetic chain. However, objective evidence linking TMJ dysfunction with foot biomechanics is limited. Aim: To investigate the association between TMJ disorders and foot weight-bearing patterns using sensor plate technology. Methods: An observational cross-sectional study was conducted on 40 male participants (20 with clinically diagnosed TMJ disorders and 20 healthy controls; mean age 24.3 ± 5.5 years). TMJ dysfunction was assessed using the Helkimo Index and Jaw Functional Limitation Scale (JFLS). Foot biomechanics were evaluated using the KAN OHM 6000 sensor plate during static and dynamic tasks. Parameters included plantar pressure distribution, sway patterns, and gait characteristics. Results: Participants with TMJ disorders exhibited significantly greater postural deviations (65% moderate, 5% major) compared with controls. Hindfoot-dominant loading was observed in 80% of TMJ patients, accompanied by predominantly left-sided sway patterns (80%). Correlation analysis revealed significant associations between TMJ severity, history of injury, and altered foot biomechanics (r = 0.30–0.40, p < 0.05). Regression analysis confirmed TMJ severity as a predictor of hindfoot loading (β = 0.61, R² = 0.48). Follow-up assessments demonstrated improvement in plantar distribution (forefoot 44.9% → 46.8%, hindfoot 55.1% → 53.2%) and reduced sway asymmetry. Conclusion: TMJ disorders are strongly associated with altered plantar loading and lateralized balance, supporting the kinetic chain model. Incorporating plantar pressure and balance analysis into TMJ rehabilitation may enhance diagnosis and treatment outcomes.